A Perovskite Light‐Emitting Device Driven by Low‐Frequency Alternating Current Voltage. Issue 16 (31st May 2018) - Liu, Xuhai; Yu, Dejian; Huo, Chengxue; Song, Xiufeng; Gao, Yujie; Zhang, Shengli; Zeng, Haibo
Abstract: Halide perovskite microplatelets (HPeMs) with ultrahigh crystallinity and large lateral dimension provide a good potential for realizing new micrometer‐scale light sources. However, the difficulty of obtaining uniform microplatelet thin films imposes the impediment for getting light sources in the conventional vertical configuration. Here, bright electroluminescence (EL) from a light‐emitting device based on solution‐processed large HPeMs is obtained using alternating current (AC) voltage in a planar device configuration. The bright and stable EL driven by 50 Hz demonstrates that this AC‐driven light‐emitting device can directly couple with household power supplies, thereby simplifying the electrical circuit modulation. The low‐frequency‐driven capability can be originated from the high charge carrier mobility and long carrier lifetime in perovskites, i.e., the hole accumulation can be reduced near the metal electrode to allow more hole injection, and more long‐lifetime holes can wait for injected electrons to recombine. Moreover, the shift of peak position and full‐wavelength‐at‐half‐maximum in the temperature‐dependent EL spectra reveals that the electric‐induced ionized scattering centers and related ion migration might have been neglected in the widely studied temperature‐dependent photoluminescence measurements. This work demonstrates an alternative operating mechanism and light‐emitting device configuration for obtaining EL from perovskites, offering a new manner to get novel micrometer‐scale perovskite light sources. Abstract : Electroluminescence (EL) is obtained from a light‐emitting device based on solution‐processed large CsPbBr3 microplatelets using alternating current (AC) voltage. The EL driven by 50 Hz suggests that this AC‐driven light‐emitting device can directly couple with household power supplies, thereby simplifying the electrical circuit modulation. The light emission at 50 Hz is still tunable after storing the device for nearly three months.